Tafsir ath - thabari - 397012 Abu Jafar Muhammad Bin Jarir Ath - Thabari (Jakarta, IO : Pustaka Azzam, 2007)
v. 1. -- v. 2. -- v. 3. -- v. 4. -- v. 5. -- v. 6. -- v. 7. An-Nisaa' -- v. 8. An-Nisaa' dan Al Maa'idah -- v. 9. Al Maa'idah dan Al An'aam -- v. 10. Al An'aam dan Al A'raaf -- v. 11. Al A'raaf -- v. 12. Al Anfaal dan At-Taubah -- v. 13. At-Taubah, Yuunus dan Huud -- c. 14. Huud, dan Yuusuf -- v. 15. Yuusuf, Ar-Ra'd, Ibraahiim, dan Al-Hijr -- v. 16. An-Nahl dan Al Israa' -- v. 17. Al Kahfi, Maryam dan Thaahaa